Greece : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
Fiscal expansion after euro accession led to a buildup of large economic imbalances, and a program to make fiscal policy and the fiscal and debt position sustainable was initiated. However, the program saw opposition from the outset and structural reforms stalled, which unsettled the investment climate. The Greek government's determination to push ahead with reforms has seen progress in fiscal adjustment and perseverance of the financial sector. However, the social cost of the recession has been very high, and the current program can only succeed if policymakers address the root causes.